Measurement of the sixth-order cumulant of net-proton multiplicity distributions in Au + Au collision at √sNN=27, 54.4, and 200 GeV at RHIC - Abdallah, Mohamed Samy; Deppner, Ingo Martin; Herrmann, Norbert; Söhngen, Yannick; Weidenkaff, Philipp (Physical review letters, 2021)
According to first-principle lattice QCD calculations, the transition from quark-gluon plasma to hadronic matter is a smooth crossover in the region μB≤Tc. In this range the ratio, C6/C2, of net-baryon distributions are predicted to be negative. In this Letter, we report the first measurement of the midrapidity net-proton C6/C2 from 27, 54.4, and 200 GeV Au+Au collisions at the Relativistic Heavy Ion Collider (RHIC). The dependence on collision centrality and kinematic acceptance in (pT, y) are analyzed. While for 27 and 54.4 GeV collisions the C6/C2 values are close to zero within uncertainties, it is observed that for 200 GeV collisions, the C6/C2 ratio becomes progressively negative from peripheral to central collisions. Transport model calculations without critical dynamics predict mostly positive values except for the most central collisions within uncertainties. These observations seem to favor a smooth crossover in the high-energy nuclear collisions at top RHIC energy.
Gesehen am 18.08.2022
Im Titel steht der Ausdruck "sNN" unter dem Wurzelsymbol, dabei ist "NN" ist tiefgestellt